2011
DOI: 10.2165/11586850-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medication Review on Drug-Related Problems in Patients Using Automated Drug-Dispensing Systems

Abstract: This study shows that patients using automated drug dispensing have a high number of DRPs. Medication review decreases the number of DRPs among these patients. We recommend that all patients with automatic drug dispensing should have a thorough medication review by pharmacists and prescribers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 26 publications
5
101
1
2
Order By: Relevance
“…This finding is in line with the idea of ADD as a preventive intervention targeted to patients with a higher risk of drug-related problems, medication errors, or inappropriate drug use. There is recent evidence that ADD patients’ quality of pharmacotherapy may be improved by regular medication reviews integrated with ADD [24]. Medication reviews may also reduce the risk of unchanged medications for unnecessarily long periods, once a patient is enrolled in the ADD procedure [15].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the idea of ADD as a preventive intervention targeted to patients with a higher risk of drug-related problems, medication errors, or inappropriate drug use. There is recent evidence that ADD patients’ quality of pharmacotherapy may be improved by regular medication reviews integrated with ADD [24]. Medication reviews may also reduce the risk of unchanged medications for unnecessarily long periods, once a patient is enrolled in the ADD procedure [15].…”
Section: Discussionmentioning
confidence: 99%
“…Within focus groups conducted post-trial, participating pharmacists also admitted to using the 'Other' sub-categories or not recording the intervention at all if they found the intervention hard to classify. The DOCUMENT classification system has recently gained some international acceptance, with Kwint et al [22] modifying the original PROMISe II DOCUMENT system (as shown in Table 1) for use in the Netherlands. Interestingly, the authors have made changes to the original DOCUMENT system that are similar to those made for PROMISe III.…”
Section: Discussionmentioning
confidence: 99%
“…10 De bekendste en meestgebruikte GDV in Nederland is de medicatie op rol ('Baxter'), waarbij de geneesmiddelen door een robot in plastic zakjes worden gedaan, die op een rol worden aangeleverd. [20][21][22] Er is een sterke groei van het aantal GDV-gebruikers:…”
Section: Optimaliseren Geneesmiddelengebruik Door Ouderenunclassified